PENGARUH BIAYA OPERASIONAL TERHADAP NET PROFIT (LABA BERSIH) PERUSAHAAN LQ 45 YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2015 – 2017 - RIA FITRIANI; ERIANDI ERIANDI; SITI NURYANI (BALANCING: Accountancy Journal, 2021)
The main objective of the research is to find out the influence of operational cost to net profit at LQ 45 companies in Bursa Efek Indonesia. The method used in this research was quantitative descriptive. The data collection was used in this research was done by documentation, and literature study. The data which used was income statement company, meanwhile the technique used to analyze the data were the normality test, coefficient of autocorrelation, coefficient of heteroscedasticity, coefficient hypothesis ( coefficient T), simple linear regression analysis and coefficient of determination. Based on the results of this study showed that t value 11,609 ( t value 11,609 t table 2,010) and a sig value of 0,00 0,05. Thus is rejected. This means that there is a significant influence on Operating Costs on Net Profit for LQ 45 Companies Bursa Efek Indonesia periode 2015 – 2017